Inhibition of the corrosion of an aluminum alloy by products of microbiological synthesis - Zin, I.M.; Korniy, S.A.; Karpenko, O.V.; Tymus, M.B.; Khlopyk, O.P.; Pokhmurskii, V.I. (Reports of the National Academy of Sciences of Ukraine, 2018)
The surface-active product of the Pseudomonas sp. PS-17 strain biosynthesis (ramnolipid biocomplex) can provide the effective corrosion inhibition of the mechanically activated surface of aluminum alloys in a synthetic acid rain. The efficiency of the inhibition becomes stronger with increasing the biosurfactant concentration. However, above the critical micelle concentration (CCM), the further improvement in the inhibition is minor. The mechanism of corrosion inhibition consists in the adsorption of biosurfactant molecules on the alloy surface with the formation of a barrier film and in the formation of a low-soluble complex compound by the interaction of rhamnolipids with aluminium ions on anode metal areas. Adding the biosurfactant to the corrosive environment increases the rate of protective film recovery on the aluminum alloy at the repassivation stage by 2 … 4 times as compared with the uninhibited solution.